Arts’s Fight for Life or the Triumphant End of the Avant-Garde - Ірина Данілова (Культура і мистецтво у сучасному світі)
The aim of the article is to outline a logical sequence of events that led to radicalism in the art of the 19th and 20th centuries by studying the connections between art, life (reality), and science and technology. From the mid-nineteenth century through the 1970s, art acquired a unique quality: it rapidly radicalised, creating a number of alternative art practices, such as impressionism, abstractionism, cubism, ready-made, etc. Before that, except for random individual phenomena, art for centuries was just changing styles: Baroque, Rococo, Classicism. Results. The article identifies the cause for the revolutionary avant-garde trends in art and the reason for the end of the revolutionary era. It presents a view based on art’s relations with life in competition with science and technology that had different effects on art, ranging from influentially adaptive to revolutionary rebellious. The scientific significance of this study is its innovative approach to the consideration of factors of the emergence and development of avant-garde trends in the art of the 19th and 20th centuries. The rational study and comparable analyses of events in science/ technology and art in relation to life (reality) offers an inventive and coherent reason for the appearance and disappearance of avant-guard art. Conclusions. This article identifies the cause for the revolutionary avant-garde trends in art and the reason for the end of the revolutionary era. It presents a unique view based on art’s relations with life in competition with science and technology and shows how an inadvertent battle of art for life (reality) with photography, film and television triumphed in the twentieth century and broke the very possibility of further revolutionary changes.